Vivências e reescrituras do espaço arquitetônico da PUC-SP: o campus Monte Alegre - Fabbris, Renata Adriana (2025)
The purpose of this research is to understand how the architecture of PUC-SP's Monte Alegre campus, as an enunciating and acting subject, contributes to the apprehension and production of meaning in university experiences. It is based on the concepts of French semiotics, especially those postulated by Greimas edifying groups of semiotic theory, its developments by Landowski with the regimes of interactions and meanings and the semiotics of visuality by Floch and Oliveira. The neighborhood that shelters the campus has undergone major transformations, changing its morphology, population density and types of commerce. In this context of erasures and rewritings, the campus, which began its history in a former convent, remains as a permanence, in continuous interaction and reinvention of its spaces, marking its identity in the built space and contributing to the construction of the identity of its community, thus justifying the importance of this research by collaborating with studies in the semiotics of space and university campuses. The hypothesis is that certain features of the architecture contribute to the practice of certain types of interaction and meaning regimes, but also that some of these spaces that are intensely practiced can lead to new meanings and uses. Through architectural surveys and observation diaries, it was possible to analyze this syncretic language object as a whole and break it down, understanding the meanings in the rewritings and life practices established in the various environments offered by the University. The conclusion is that in its syntax and semantics, architecture brings fundamental elements to the practices of university life, contributing to the different regimes of interaction and the production of meaning, being a participant in the construction of the collective, individual and neighborhood university identity, as a center for the construction, circulation and transmission of knowledge, confirming the hypothesis raised